Wisteria: Belladona # 3 - Grace, Adalyn (New York : Little, Brown and Company, 2024)
"When headstrong Blythe Hawthorne finds herself bound to the insufferable deity Fate, she begins to uncover the truth about their connection and her own astonishing powers"--.
new ya book 2024 fall.
Ages 14 and up.
Keywords: Ability -- Fiction; Fantasy; Magic -- Fiction; Fate and fatalism -- Fiction; Novels; Fantasy fiction